ANALYSIS ON COMPARATIVE ADVANTAGE OF AGRICULTURAL SECTOR IN KULON PROGO REGENCY - Evita Hanie Pangaribowo; Rika Harini (Faculty of Geography, Universitas Gadjah Mada, 2009)
Comparative advantage is measured using economic and social values. Comparatively superior commodities mean that they are produced in an economically efficient way. Agricultural sector is the one that is prioritized in Kulon Progo Regency and, thus, purposively that region is employed as the sample of this study. Research is based on the analysis of secondary and primary data collected through interviews with 60 respondents. The respondents consist of 2 groups of rice field farmers in Lendah Sub-district, Kulon Progo Regency, which constitutes the predominant crop field area. The analysis is conducted descriptively using the Policy Analysis Matrix method. Based on the cost-benefit analysis, rice commodity agribusiness in Kulon Progo regency has privately generated average financial profit amounting to Rp. 2, 18 million per season. Meanwhile, it is socially and economically generating relatively large profit amounting to Rp. 4.58 million per season. The level of rice field economic efficiency amounts to 0.747. These values demonstrated that rice agribusiness has comparative advantage which means that producing rice commodities in Kulon Progo Regency is more cost effective than importing them.